2005
DOI: 10.1007/s10067-005-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of patients with adult-onset Still’s disease compared with systemic juvenile idiopathic arthritis

Abstract: Adult-onset Still's disease (AOSD) has often been regarded as the adult spectrum of systemic juvenile idiopathic arthritis (sJIA). The present study aims to compare the clinical and laboratory features, the disease course and the response to treatment in patients having AOSD with those having sJIA. Retrospective review of all available data that were filled out by adult and paediatric rheumatologists from six centers using a standard data extraction form was performed. A total of 95 patients with AOSD and 25 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 15 publications
5
55
3
3
Order By: Relevance
“…In addition to clinical symptoms, most laboratory abnormalities were common to both patients with s-JIA and those with AOSD. However, serum ferritin levels were significantly higher in patients with AOSD than in those with s-JIA [5,6]. These findings were comparable with those of previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition to clinical symptoms, most laboratory abnormalities were common to both patients with s-JIA and those with AOSD. However, serum ferritin levels were significantly higher in patients with AOSD than in those with s-JIA [5,6]. These findings were comparable with those of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In support of this view, the present study found no differences between these conditions except for hepatomegaly and splenomegaly, which were more frequently observed in AOSD, and arthritis, which was more frequently observed in s-JIA. Previous studies reported significant differences between s-JIA and AOSD with regard to the frequencies of fever, skin rash, and sore throat, all of which occurred more frequently with AOSD [3,6]. The enrollment of more pediatric patients in our study relative to previous studies on clinical disease expression might account for the observed discrepancies.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It occurs worldwide and has been reported from France, [5,6] Norway, [7] Japan, [8,9] Greece, [10] USA, [11] Taiwan, [12,13] Spain, [14] Korea, [15,16] China, [17,18] Turkey, [19,20] India [21,22] and Iran. [23] The disease affects young people and has a bimodal age distribution with two peaks -at 15-25 and 36-46 years of age.…”
Section: Epidemiologymentioning
confidence: 99%